P42 Recruitment strategies and lessons from the we can quit2 trial – a smoking cessation community-based cluster randomised controlled trial for women living in disadvantaged areas of ireland. (3rd September 2019) - Burke, E; O'Connell, N; Darker, C; Vance, J; Dougall, N; Bauld, L; Hayes, C
Abstract : Background: Recruitment is a challenge in community-based randomised controlled trials (RCTs). Evidence on recruitment efforts are not routinely available although they help predict rates and manage risk. This study aims to describe recruitment strategies used in the We Can Quit2 (WCQ2) study, and successes and barriers. Methods: WQC2 trial is a pilot, pragmatic, parallel-group cluster RCT delivered to women living in disadvantaged areas in Ireland. It tests the WCQ2 programme, a smoking-cessation behavioural support intervention delivered through 12-weekly group sessions, with free Nicotine Replacement Therapy, against a form of usual care. Four Local Area Advisory Groups (LAGs) were established which consist of local area stakeholders, for example the Irish Cancer Society, the HSE, community organisations, and community workers. LAGs identified four matched pairs of districts within their region (eight clusters) from which eligible women could be recruited. LAGs and the study researcher recruited participants. The recruitment target was 24–25 women in each cluster (97 per arm; 194 in total). Consent was obtained prior to cluster randomisation. Results: Participants were recruited through a variety of methods including leafleting, posters in local shops and community services, information stands at local public events and in facilities like creches, and through traditional and social media, e.g. local radio and targeted Facebook advertisements. The trial was promoted at community employment schemes, and parenting groups. Barriers to recruitment included certain times of year, like public holidays. We employed the National Adult Literacy Agency to improve readability of participant documents but later, to comply with GDPR guidelines, we lengthened our Participant Information Leaflet, which some women found off-putting. The trial was co-ordinated at a prestigious university and some eligible women expressed concern that they might be judged by researchers. In response, advertising through the university's website was discontinued. Several strategies were successful. LAG members applied in-depth knowledge of local communities to target recruitment to eligible women. Advertising via social media helped recruit younger women. Using a centrally-located, well-known building within each district, with good transport links, improved attendance at consent meetings, particularly important for those with mobility issues. Recruitment occurred over four waves, allowing the application of iterative learning. Conclusion: Recruitment strategies in the WCQ2 trial had variable success. Community-based trials have specific challenges such as the availability and suitability of local resources and the regulatory environment. The early and active engagement of local stakeholder groups with in-depth knowledge of communities is important, as well as the application of iterative learning.